2008
DOI: 10.1088/1742-5468/2008/04/p04005
|View full text |Cite
|
Sign up to set email alerts
|

The shape of invasion percolation clusters in random and correlated media

Abstract: The shape of two-dimensional invasion percolation clusters are studied numerically for both nontrapping (NTIP) and trapping (TIP) invasion percolation processes. Two different anisotropy quantifiers, the anisotropy parameter and the asphericity are used for probing the degree of anisotropy of clusters. We observe that in spite of the difference in scaling properties of NTIP and TIP, there is no difference in the values of anisotropy quantifiers of these processes. Furthermore, we find that in completely random… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The invasion percolation model has a number of structural statistical features and has been studied for anisotropic cluster effects [13]. We can label and measure the cluster size distribution in our model.…”
Section: Discussionmentioning
confidence: 99%
“…The invasion percolation model has a number of structural statistical features and has been studied for anisotropic cluster effects [13]. We can label and measure the cluster size distribution in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigations show that in general, the introduction of long-range correlations into a medium, makes the shape of SSC more anisotropic. 27 …”
Section: The Anisotropy Of Sample Spanning Clustermentioning
confidence: 99%
“…The shape of clusters in percolation type models is an interesting physical property. Numerical simulations on random models has revealed that percolation clusters at the percolation threshold are asymmetric [1,2,3,4,5] which is a significant result, especially because of the close connection between percolation model and the theory of second-order phase transition [1,6].…”
Section: Introductionmentioning
confidence: 99%